Intrathecal Morphine Administration Does Not Affect Survival After Liver Resection for Hepatocellular Carcinoma. (September 2019) - Smith, Natalie K.; Demaria, Samuel; Katz, Daniel; Tabrizian, Parissa; Schwartz, Myron; Miller, Joanna C.; Hill, Bryan; Cardieri, Brielle; Kim, Sang J.; Zerillo, Jeron
Introduction . Opioids may influence tumor recurrence and cancer-free survival in hepatocellular carcinoma (HCC). The relationship between intrathecal morphine administration, tumor recurrence, and patient survival after hepatectomy for HCC is unknown. Patients and Methods . This single-center, retrospective study included 1837 liver resections between July 2002 and December 2012; 410 cases were incorporated in the final univariate and multivariate analysis. Confirmatory propensity matching yielded 65 matched pairs (intrathecal morphine vs none). Primary outcomes were recurrence of HCC and survival. Secondary outcomes included characterization of factors associated with recurrence and survival. Results . Groups were similar except for increased coronary artery disease in the no intrathecal morphine group. All patients received volatile anesthesia. Compared with no intrathecal morphine (N = 307), intrathecal morphine (N = 103) was associated with decreased intraoperative intravenous morphine administration (median difference = 12.5 mg; 95% confidence interval [CI] = 5-20 mg). There was no difference in blood loss, transfusion, 3- or 5-year survival, or recurrence in the univariate analysis. Multivariate analysis identified covariates that significantly correlated with 5-year survival: intrathecal morphine (hazard ratio [HR] = 0.527, 95% CI = 0.296-0.939), lesion diameter (HR = 1.099, 95% CI = 1.060-1.141), vascular invasion (HR = 1.658, 95% CI = 1.178-2.334), and satellite lesions (HR = 2.238, 95% CI = 1.447-3.463). Survival analysis on the propensity-matched pairs did not demonstrate a difference in 5-year recurrence or survival. Discussion and Conclusion . Multivariate analysis revealed a significant association between intrathecal morphine and 5-year survival. This association did not persist after propensity matching. The association between intrathecal morphine and HCC recurrence and survival remains unclear and prospective work is necessary to determine whether an association exists.